Perumusan Rekomendasi Strategi Bisnis Pie Susu Dewata (PT. Angga Cahaya Dewata) Menggunakan Business Model Canvas dan Analisis SWOT [Formulation of Business Strategy Recommendations for Pie Susu Dewata (PT. Angga Cahaya Dewata) Using Business Model Canvas and SWOT Analysis] - Hakiki, Moh. Saiful; Anggraini, Dwi Aprilia; Mawli, Rizka Efi; Yustiana, Dewi; Fatimah, Nuzulul (Indonesia Berdaya, 2025)
One of the three implementations of the Tridharma of Higher Education is Community Service (PKM/Abdimas), which aims to offer solutions for accelerating business growth. One of the related topics is business strategy management, both for MSMEs and large-scale enterprises. This Abdimas activity is an analysis and synthesis of observations and studies regarding the business strategy of Pie Susu Dewata, Bali. Pie Susu Dewata is a cake product developed by PT Angga Cahaya Dewata and has become one of the leading pie susu products in Bali. The strategic management method we recommend uses the principles of the Business Model Canvas (BMC) and SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats) to describe the business model implemented by Pie Susu Dewata. In the BMC analysis, elements such as Customer Segments, Value Propositions, Channels, Revenue Streams, Key Resources, Customer Relationships, Key Activities, Key Partnerships, and Cost Structure are considered. This activity is expected to improve literacy on strategic management and raise awareness of the urgency and relevance of this field. The findings have a positive impact on the business development of Pie Susu Dewata, particularly in equipping management with up-to-date managerial insights. Abstrak. Satu dari tiga implementasi Tridharma Perguruan Tinggi adalah kegiatan Pengabdian Kepada Masyarakat (PKM/Abdimas) yang bertujuan untuk menawarkan solusi bagi akselerasi pertumbuhan usaha, di mana salah satu topik terkait adalah mengenai manajemen strategi dari usaha, baik berskala UMKM, maupun di skala besar. Kegiatan Abdimas ini merupakan analisis dan sintesis dari hasil pengamatan dan kajian mengenai strategi bisnis dari Pie Susu Dewata, Bali. Pie Susu Dewata adalah produk kue yang dikembangkan oleh PT Angga Cahaya Dewata dan menjadi salah satu produk pie susu terkemuka di Bali. Metode manajemen strategi yang kami rekomendasikan menggunakan prinsip Bisnis Model Canvas (BMC) dan Analisis SWOT (Strength, Weakness, Opportunity, Threat) dalam mendeskripsikan model bisnis yang yang dijalankan oleh Pie Susu Dewata. Dalam analisis BMC, dipertimbangkan unsur-unsur seperti Customer Segments, Value Propositions, Channels, Revenue Streams, Key Resources, Customer Relationships, Key Activities, Key Partnership, dan Cost Structure. Kegiatan diharapkan meningkatkan literasi mengenai manajemen strategi dan menumbuhkan kesadaran akan urgensi dan relevansi dari bidang manajemen strategi ini. Temuan memberikan dampak positif bagi pengembangan usaha bagi Pie Susu Dewata, khususnya dalam membekali pengelola dengan informasi wawasan terkini di topik manajerial.